2004
DOI: 10.1179/joc.2004.16.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Trimethoprim-Sulfamethoxazole, Cephadroxil and Cefprozil as Prophylaxis for Recurrent Urinary Tract Infections in Children

Abstract: The aim of this study was to compare the efficacy of prophylactic trimethoprim-sulfamethoxazole (TMP/SMZ), cefprozil and cephadroxil treatments in children who have recurrent urinary tract infection, but no urinary tract pathology. After acute urinary tract infections (UTIs) were treated, the patients were divided into 3 groups randomly and TMP/SMZ was given to 21 patients, cephadroxil was given to 25 patients and cefprozil was given to 34 patients for 3 months--one dose at night. All patients were followed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…Few studies have compared the effectiveness of different antibiotics in preventing recurrent UTIs in children. [93][94][95][96][97] Nitrofurantoin was found to be more effective than trimethoprim-sulfamethoxazole in patients with urological abnormalities and young patients aged 1 to 5 years with normal urinary tract system. 93,94 Other studies that included patients without urinary tract abnormalities showed that nitrofurantoin was as efficacious as trimethoprim, cefixime, and pivmecillinam (an extendedspectrum penicillin, not available in the United States).…”
Section: Prophylaxismentioning
confidence: 99%
“…Few studies have compared the effectiveness of different antibiotics in preventing recurrent UTIs in children. [93][94][95][96][97] Nitrofurantoin was found to be more effective than trimethoprim-sulfamethoxazole in patients with urological abnormalities and young patients aged 1 to 5 years with normal urinary tract system. 93,94 Other studies that included patients without urinary tract abnormalities showed that nitrofurantoin was as efficacious as trimethoprim, cefixime, and pivmecillinam (an extendedspectrum penicillin, not available in the United States).…”
Section: Prophylaxismentioning
confidence: 99%
“…[7] Over the years, treatment of urinary tract infection (UTI) has thrown up a lot of challenges due to the increasing level of antimicrobial resistance. [8] Varying and high levels of multiple resistance of uropathogenic Enterococcus species and other urinary bacterial isolates to quite a large number of antibiotics commonly used in treatment of UTIs, have been encountered. Effective management of these infections is often hampered by the lack of adequate facilities for proper microbial isolation as well as for their antimicrobial susceptibility testing.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Trials in Japan and Turkey showed that low-dose cephalosporin treatment could effectively reduce the risk of recurrent UTIs in children. 7,8 These results suggest that cephalosporins can be an alternative choice for prophylactic treatment. Antibiotic prophylaxis with cephalosporins for VUR has been favored by many pediatric nephrologists and urologists in Japan 7 and elsewhere, including Taiwan.…”
mentioning
confidence: 95%